Estimates of Alcohol Use and Clinical Treatment Needs Among Homosexually Active Men and Women in the U.S. Population - Cochran, Susan D. (2000)
Concerns about dysfunctional alcohol use among lesbians and gay men are longstanding. The authors examined alcohol use patterns and treatment utilization among adults interviewed in the 1996 National Household Survey on Drug Abuse. Sexually active respondents were classified into 2 groups: those with at least 1 same-gender sexual partner (n = 194) in the year prior to interview and those with only opposite-gender sexual partners (n = 9,714). The authors compared these 2 groups separately by gender. For men, normative alcohol use patterns or morbidity did not differ significantly between the 2 groups. However, homosexually active women reported using alcohol more frequently and in greater amounts and experienced greater alcohol-related morbidity than exclusively heterosexually active women. Findings suggest higher risk for alcohol-related problems among lesbians as compared with other women, perhaps because of a more common pattern of moderate alcohol consumption.